The Relationship Economic Complexity and Education Expenditure: A Empricial Analysis on South Korea - Kurt, Ünzüle (International Journal of Economics and Financial Issues, 2019)
South Korea exhibited a noteworthy economic performance with development policies it carried out in 1962. The resources of this economic leap have been widely the subject of researches in the literature. It has been taken as an sample experience especially in the development projections of developing ccountries. This country, which was in a poor country position by 1960s has managed to get to developed country position within the period of 50 years. The relevant studies have shown that the sources of South Korean economic growth and development are the importance attached to education, innovation and R&D studies and development plans including structural changes in these areas. The production of products with high value added and having multinational companies producing these products, which is one of the most important sources which provide for developed countries to have a competitive advantage in the world economy, was considered significant for South Korean economic growth and development in the present study. In this context, the effects of expenditures for higher education on industrial production through the production of products with high value added was investigated. It was found as a result of this empirical study, in which Johenson cointegration analysis and VECM model and Granger casualty methods were used, covered 1970-2015 period that educational expenditures has increased industrial production through econpmical complexity. Keywords: South Korea, Economic Complexity, education expenditure JEL Classifications: H52, I2 DOI: https://doi.org/10.32479/ijefi.7422